METODE GLENN DOMAN : PERMAIANAN MENGOPTIMALKAN FONDASI LITERASI ANAK USIA DINI - Niyati; Handayani, Iys Nur (ALAYYA : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The Glenn Doman play-based method is an early stimulation approach emphasizing systematic visual and language exposure to optimiz children’s brain development. This studyaims to analyze the affectivenees of the Glenn Domanmethod the strengthening early childhood literacy foundations.early literacy empompasses not only rading skills but alsolanguage development, memory, concentration, and learning motivation. This method utilizes word cards (flascard), brief yet consistent repetition, and a joyful, pressure –free learning atmosphere. The research employs a literaturw review approach and observational analysis of lerarningpractices involving children aged 5-6 yeart. The findings indicate that conci implementationof the Glen Doman method enhances vocabulary recognition, early skill, and children’s confidence in interacting, withwritten language symbols,Furthemore, this approach fosters parental involvement in the learning process, creating a positive leraracy environment at home. Through the process of results and discussion, it can be concluded that the literacy ability of children in study increased as seen from the data in cycle I with the criteria developing as expected reaching 6 students or 37,5% and data in cycle II increasing to 13 studentsor 81,25 %.